Reflectometric measurements of polarization properties in optical fiber links using Polarimetric Optical Time Domain Reflectometry (POTDR) - Dong, Hui (2011)
Polarimetric optical time-domain reflectometry (POTDR) was proposed in 1981 for measuring the spatial distributions of local polarization properties of single-mode fibers (SMF). This PhD research project aims to investigate some fundamental issues in POTDR technology and the main achievements are summarized as follows. Firstly, to improve the measurement accuracy, the optimizations of input states of polarization (SOP) and the polarimeter used in POTDR are investigated theoretically. Results show that 1) for the measurement of the 33× Mueller matrix of a pure birefringent SMF system, using two orthogonal input SOPs will statistically deliver the best measurement accuracy. 2) for the measurement of the 44× Mueller matrix of a SMF system having both birefringence and polarization dependent loss (PDL), the three optimized input SOPs are equally-spaced on the Poincaré sphere and centered on the reversed PDL vector of the system under test. 3) For the type of polarimeter commonly used in POTDR systems, when thermal noise is dominant in the photodetector and angular orientation errors can be neglected, the optimum angles of the waveplate and the polarizer can be found to minimize the SOP measurement noise.These conclusions are especially useful for optimizing a POTDR system since POTDR signals are quite noisy. Secondly, novel approaches for spatially- and spectrally-resolved polarization mode dispersion measurement techniques are proposed in SMF systems without and with PDL. The experimental results are also presented to confirm the validity of the proposed techniques. Thirdly, a novel approach for single-end PDL measurements in SMF links is demonstrated theoretically and experimentally. Further, we demonstrate by simulation that this technique has the potential to be extended to measure the PDL distribution in a SMF link.